Protective Effects of Myxobacterial Extracts on Hydrogen Peroxide-induced Toxicity on Human Primary Astrocytes. (10th February 2019) - Dehhaghi, Mona; Tan, Vanessa; Heng, Benjamin; Mohammadipanah, Fatemeh; Guillemin, Gilles J.
Graphical abstract: Highlights: Metabolites of myxobacteria reduced the ROS formation in astrocytes. Myxobacterial extracts restored the cellular glutathione level in astrocytes. Myxobacterial extracts reduced iNOS and PARP1 activities under oxidative stress. Abstract: Astrocytes, the main non-neuronal cells in the brain, have significant roles in the maintenance and survival of neurons. Oxidative stress has been implicated in various neurodegenerative disorders such as Alzheimer's disease (AD), amyotrophic lateral sclerosis (ALS), and Parkinson's disease (PD). Myxobacteria produce a wide range of bioactive metabolites with notable structures and modes of action, which introduce them as potent natural product producers. In the present study, we evaluated the effects of myxobacterial extracts on hydrogen peroxide (H2 O2 )-mediated toxicity on primary human astrocytes. We showed that myxobacterial extracts could decrease the formation of reactive oxygen species (ROS), nitric oxide (NO) production, and cell death assessed by the release of lactate dehydrogenase (LDH). Myxobacterial extracts were also able to reduce the nitric oxide synthase (NOS) activity. The extracts reduced the oxidative effect of H2 O2 on over-activation of poly (ADP-ribose) polymerase (PARP1), therefore preventing the cell death by restoring the NAD + levels. In addition, myxobacterial extracts ameliorated the oxidative stress by increasing the glutathione level in cells. The overall results showed myxobacterial extracts, especially from the strains Archangium sp. UTMC 4070 and Cystobacter sp. UTMC 4073, were able to protect human primary astrocytes from oxidative stress.